The rebels : Elizabeth Warren, Bernie Sanders, Alexandria Ocasio-Cortez, and the struggle for a new American politics - Green, Joshua, 1972- (The Penguin Press, 2024)
"In his classic book Devil's Bargain, Joshua Green chronicled how the forces of economic populism on the right, led by the likes of Steve Bannon, turned Donald Trump into their flawed but powerful vessel. In The Rebels, he gives an epic account of the long struggle that has played out in parallel on the left, told through an intimate reckoning with the careers of the three political figures who have led the charge most prominently. Based on remarkable inside sourcing and razor-sharp analysis, The Rebels uses the grand narrative of a political party undergoing tumult and transformation to tell an even larger story about the fate of America. For many years, as Green recounts, the Democrats made their bed with Wall Street and big tech, relying on corporate money for electioneering and embracing the worldview that technological and financial innovation and globalization were a powerful net good, a rising tide lifting all boats. Yes, there were howls of pain, but they were written off by most of the elites as the moaning of sore losers mired in the past. There were always some Democratic politicians representing the old labor base who resisted the new dispensation, but these figures never made it very far on a national level. For one thing, they didn't have the money. But as income inequality ballooned, widening the gulf between the wealthy elite and everyone else, pressures began to build. With the 2008 crisis, those forces finally erupted into plain sight, turning this book's protagonists into national icons. At its heart, The Rebels tells the riveting human story of the rise and fight of Elizabeth Warren, Bernie Sanders, and Alexandria Ocasio-Cortez from the financial crisis on, as outrage over the unfairness of the American system formed a flood tide of political revolution. That same tide that would sweep Trump into office was blunted on the left, as the Democratic party found itself riven by culture war issues between its centrists and its progressives. But the winds behind economic populism still howl at gale force. Whether the Democrats can bridge their divisions and home in on a vision that unites the party, and perhaps even the country, in the face of the most violently deranged political landscape since the Civil War will be the ultimate test of the legacies of all three characters" --